(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Methylin compounds, characterized by the presence of a methylene bridge (-CH2-) in their structure, are of considerable interest to modern pharmacology due to their wide range of biological activity. Historically, many of these compounds, both synthetic and natural, have found use in medical practice as antiseptics, dyes, and antimicrobials. However, in recent decades, an in-depth study of their pharmacodynamics has opened up new frontiers for their therapeutic use, in particular in the field of protecting the liver from toxic damage. This review summarizes the current data on the pharmacological properties and mechanisms of action of this class of compounds.